2019
DOI: 10.1186/s40659-019-0224-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glutamine deprivation on oxidative stress and cell survival in breast cell lines

Abstract: Background Tumourigenic cells modify metabolic pathways in order to facilitate increased proliferation and cell survival resulting in glucose- and glutamine addiction. Previous research indicated that glutamine deprivation resulted in potential differential activity targeting tumourigenic cells more prominently. This is ascribed to tumourigenic cells utilising increased glutamine quantities for enhanced glycolysis- and glutaminolysis. In this study, the effects exerted by glutamine deprivation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 50 publications
(64 reference statements)
6
33
0
Order By: Relevance
“…In vitro, indoxyl sulfate increases reactive oxygen species (ROS) production of tubular cells and promotes NADPH oxidase activity in endothelial cells, which may further protect the brain by maintaining glutathione reductase activity. Glutamine is a major nitrogen carrier and a carbon substrate for anabolic processes in cancer cells, and it may protect rats from oxidative stress [27]. Similarly, glutathione, which is the major redox couple in animal cells [28], was also increased.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…In vitro, indoxyl sulfate increases reactive oxygen species (ROS) production of tubular cells and promotes NADPH oxidase activity in endothelial cells, which may further protect the brain by maintaining glutathione reductase activity. Glutamine is a major nitrogen carrier and a carbon substrate for anabolic processes in cancer cells, and it may protect rats from oxidative stress [27]. Similarly, glutathione, which is the major redox couple in animal cells [28], was also increased.…”
Section: Biomed Research Internationalmentioning
confidence: 99%
“…This results in deprivation of these exogenously supplied nutrients, and thus inhibits tumour growth 24 . Deprivation of amino acids including asparagine, 25 arginine, 26 glutamine, 27 methionine 28,29 and phenylalanine 30 has been tested for cancer treatment in experimental models. As we have observed that high expression levels of tRNA‐Lys‐CUU potentially associates with poor outcomes in HCC patients, we tested whether deprivation of the substrate lysine functionally affects HCC cells in experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose shortage has been shown to induce cell cycle arrest [131] and apoptotic cell death [132,133] in in-vitro cancer models. In the same way, glutamine deficiency exerts the same effect on tumoral cells: in-vitro studies conducted on neuroblastoma and breast cancer cell lines have shown that glutamine deprivation leads to apoptosis [134] and proliferation arrest [135], respectively. On top of that, severe hypoxia conditions have been shown to promote cancer cell death in in-vitro cancer cell lines [136].…”
Section: Metabolic Reprogramming In Epithelial To Mesenchymal Transitionmentioning
confidence: 97%